Cloning, Exogenous Expression and Function Analysis of Interferon–γ from Gadus macrocephalus - Jielan Jiang; Jie Gu; Aijun Zhan; Mingguang Mao; Yumeng Liu; Haishan Wang; Yunxiang Mao (Viruses, 2022)
Interferon γ (IFN–γ) is now considered to be one of the key molecules in the regulation of innate and adaptive immunity. The function of IFN–γ is best described in humans, but less of IFN–γ in fish species has been described at protein level. In the present study, IFN–γ from Gadus macrocephalus (GmIFN–γ) has been examined in terms of bioinformatics, prokaryotic expression, yeast expression, antiviral activity and immune regulatory function. The cDNA of GmIFN–γ contains an open reading frame of 570 nucleotides, coding 189 amino acids. The mature protein contains a nuclear localization signal motif and an obvious IFN–γ signature sequence at the C-terminal. GmIFN–γ is very similar to that of Atlantic cod, with homology up to 89.89%, but less than 32% to other species. GmIFN–γ can be detected in the gills, spleen, intestine, brain and kidney. Interestingly, during early development, a strong signal of GmIFN–γ was not detected until 40 days post hatching. Prokaryotic expression plasmid pET–32a–GmIFN–γ was constructed, and the expression products in BL21 were confirmed by Mass Spectrometry. Meanwhile, the plasmid pGAPZA–GmIFN–γ with Myc tag was constructed and transmitted into Pichia pastoris yeast GS115, and the products were tested using Western blot. The purified GmIFN–γ from either BL21 or yeast has a strong antivirus (Spring viremia of carp virus) effect. The vector of pcDNA3.1–GmIFN–γ was expressed in EPC cell lines; high transcript levels of MHC class I chain-related protein A (MICA) gene were detected; and the exogenous GmIFN–γ protein could also induce MICA expression, indicating that GmIFN–γ could stimulate immune response. The yeast GS115 with GmIFN–γ protein, which is an inclusion body, was given to zebrafish orally, and the transcript of zebrafish IFN–γ was upregulated significantly; however, genes of the interferon type–I signal pathway were not well stimulated.